Analysis of Nutritional Composition in Vegetarian Diets and Their Impact on Cardiovascular Health - Renaldi Suardina; Faisal Halim (SEED: Journal of Scientific Research, 2026)
Sprint speed is one of the crucial physical components in modern football. One method that can be used to increase sprint speed is strength training. This study aims to analyze the effectiveness of a strength training program on increasing sprint speed in football players. The research method used was an experiment with a pre-test and post-test design on a group of football players aged 18–25 years. The subjects were divided into two groups, namely the experimental group that underwent a strength training program for 8 weeks and the control group that underwent conventional training. Sprint speed data were collected using a 30-meter sprint test before and after the intervention. The results showed that there was a significant increase in sprint speed in the experimental group compared to the control group (p <0.05). These findings indicate that a strength training program has a positive impact on increasing sprint speed in football players. Therefore, it is recommended for coaches and sports practitioners to integrate strength training into training programs to improve athlete performance.